2014
DOI: 10.1123/jsep.2013-0229
|View full text |Cite
|
Sign up to set email alerts
|

Fostering a Need-Supportive Teaching Style: Intervention Effects on Physical Education Teachers’ Beliefs and Teaching Behaviors

Abstract: The present intervention study examined whether physical education (PE) teachers can learn to make use of autonomy-supportive and structuring teaching strategies. In a sample of 39 teachers (31 men, M = 38.51 ± 10.44 years) and 669 students (424 boys, M = 14.58 ± 1.92 years), we investigated whether a professional development training grounded in self-determination theory led to changes in (a) teachers' beliefs about the effectiveness and feasibility of autonomy-supportive and structuring strategies and (b) te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
125
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 165 publications
(155 citation statements)
references
References 37 publications
(56 reference statements)
8
125
0
4
Order By: Relevance
“…First, it might be important for physical education teachers to consider that those adolescents who are highly dissatisfied with their body will also be more likely to feel less competent during physical education. On the other hand, if physical education teachers manage to create lessons in which adolescents feel competent, for instance, by providing more positive feedback and clear guidelines, this could diminish adolescents' body dissatisfaction. Additionally, consideration could be given to the implementation of an Activist Approach in physical education that supports pupil engagement in physical education lessons through student centered pedagogy and pedagogies of embodiment…”
Section: Discussionmentioning
confidence: 99%
“…First, it might be important for physical education teachers to consider that those adolescents who are highly dissatisfied with their body will also be more likely to feel less competent during physical education. On the other hand, if physical education teachers manage to create lessons in which adolescents feel competent, for instance, by providing more positive feedback and clear guidelines, this could diminish adolescents' body dissatisfaction. Additionally, consideration could be given to the implementation of an Activist Approach in physical education that supports pupil engagement in physical education lessons through student centered pedagogy and pedagogies of embodiment…”
Section: Discussionmentioning
confidence: 99%
“…That is, the pre-training beliefs that participants might have about the effectiveness of proposed motivating strategies need to be addressed as they may affect participants' receptiveness to the training as well as its effectiveness (Pintrich, Marx, & Boyle, 1993). Indeed, a recent intervention study by Aelterman, Vansteenkiste, Van den Berghe, De Meyer, and Haerens (2014), showed that PE teachers' change in effectiveness beliefs regarding the provision of autonomy support was positively associated with changes in teacher-reported autonomy-supportive behaviours. Hence, it is important that teachers' beliefs are targeted in training programs for PE teachers, as was also suggested by Taylor, Ntoumanis, and Smith (2009), who demonstrated that teachers' beliefs are not always in line with their teaching approach.…”
Section: Practical Implicationsmentioning
confidence: 96%
“…Autonomysupportive versus controlling motivational styles are positively associated with children's and adolescents' need satisfaction in sport (Mouratidis, Lens, & Vansteenkiste, 2010) and PE (Mouratidis, Vansteenkiste, Lens, & Sideridis, 2008). Social agents can be trained to use an autonomy-supportive teaching style (Aelterman, Vansteenkiste, Van den Berghe, De Meyer, & Haerens, 2014;Tessier, Sarrazin, & Ntoumanis, 2010). As such, SDT is being increasingly used to inform children's school-based physical activity interventions in PE lessons (Chatzisarantis & Hagger, 2009;Lonsdale et al, 2013), non-PE curriculum lessons (Contento, Koch, Lee, & Calabrese-Barton, 2010;Pardo, Bengoechea, Julian Clemente, & Lanaspa, 2014), and after-school settings (Robbins et al, 2013;Wilson et al, 2011).…”
Section: Facilitation Of Autonomous Motivation Through Autonomysuppormentioning
confidence: 99%